Optimalisasi Ekonomi Hijau melalui Pertanian Organik dan Teknologi Hidroponik: Studi Kasus Desa Tanjung Hutan - Hardiani; Hastuti, Dwi; Parmadi; Junaidi; Hodijah, Siti (Studium: Jurnal Pengabdian Kepada Masyarakat, 2024)
Tanjung Hutan Village has great potential in developing sustainable agriculture in line with the concept of green economy. However, the challenge in adopting environmentally friendly agricultural practices is still a major obstacle. The purpose of this community service is to explore the potential of organic farming and hydroponic technology as a sustainable and efficient alternative in the context of Tanjung Hutan Village. It is hoped that by implementing this technology, Tanjung Hutan Village can improve the quality of life of its people while minimizing negative impacts on the environment. In addition, this community service aims to provide a better understanding of the potential of the green economy and the possibility of its implementation in the local context. The targeted outputs of this community service include policy recommendations that can be implemented by the local government or related institutions to support the transformation of agriculture towards a more sustainable model. In addition, it is hoped that there will be practical guidance for farmers and other stakeholders in Tanjung Hutan Village in implementing hydroponic technology and organic farming practices. Through this community service, it is hoped that a deeper understanding can be built about the relationship between the green economy, organic farming, and hydroponic technology in Tanjung Hutan Village.